Factores predisponentes de la dinámica familiar y sociocultural de la niñez que afectan la salud mental en la etapa de adultez temprana (2023)
This research focuses on the importance of development in a certain social or family context during childhood, since it is a fundamental factor in the personal structure of individuals. This research aims to investigate the family and psychosocial factors that worsen the mental health of the young adults participating in this study.